FANCI Regulates Recruitment of the FA Core Complex at Sites of DNA Damage Independently of FANCD2 - Castella, Maria (PLoS Genet, 2015)
The Fanconi anemia (FA)-BRCA pathway mediates repair of DNA interstrand crosslinks. The FA core complex, a multi-subunit ubiquitin ligase, participates in the detection of DNA lesions and monoubiquitinates two downstream FA proteins, FANCD2 and FANCI (or the ID complex). However, the regulation of the FA core complex itself is poorly understood. Here we show that the FA core complex proteins are recruited to sites of DNA damage and form nuclear foci in S and G2 phases of the cell cycle. ATR kinase activity, an intact FA core complex and FANCM-FAAP24 were crucial for this recruitment. Surprisingly, FANCI, but not its partner FANCD2, was needed for efficient FA core complex foci formation. Monoubiquitination or ATR-dependent phosphorylation of FANCI were not required for the FA core complex recruitment, but FANCI deubiquitination by USP1 was. Additionally, BRCA1 was required for efficient FA core complex foci formation. These findings indicate that FANCI functions upstream of FA core complex recruitment independently of FANCD2, and alter the current view of the FA-BRCA pathway.